The Microbiome-Gut-Brain Axis, Nutrition and Parkinson’s Disease - Guk, Jevgenija; Kaladytė Lokominienė, Rūta; Jatužis, Dalius (Neurologijos seminarai, 2024)
Parkinson’s disease (PD) is a chronic progressive neurodegenerative disorder characterised by both motor and non-motor symptoms. While most PD medications currently available can improve motor symptoms, there is currently no treatment available to halt or slow down the progression of the disease. Recently, there has been increasing focus on environmental factors in the pathophysiology of PD and their possible neuroprotective effects. According to Braak’s hypothesis, an unknown pathogen in the gastrointestinal tract may initiate the production of pathogenic α synuclein, which would subsequently spread to the central nervous system. The microbiome-gut-brain axis may be implicated in this process, whereas nutrition can be one of the modifiable regulatory variables. A variety of foods and nutrients have been suggested as either risk or protective factors based on biological theories. Although epidemiological and experimental studies in animal models have shown their neuroprotective properties, their effectiveness was not confirmed in clinical trials. However, daily food intake comprises many nutrients that can interact and produce either a synergistic or antagonistic effect on the human body. Therefore, dietary patterns that include a certain set of nutrients have recently gained increased interest as potential modifiers of disease progression and alleviators of symptoms. This article reviews the current literature on the role of different nutritional factors and diets in the pathogenesis of PD and their possible neuroprotective and symptomatic effects.
Keywords: Parkinson’s disease; microbiome-gut-brain axis; nutrition